Modeling storm surges affecting coastal communities of Batanes during Typhoon Meranti - Ferrer, Joaquin Vicente C.; Camelo, Jeane B. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
On September 10 to 15 of 2016, Typhoon Meranti (Ferdie) traversed the Northern Pacific Basin, affecting the Batanes Islands as it passed over Itbayat island. The typhoon left a casualty and more than Php 244.6 million in damages to houses and communities. The Batanes Islands are remote and exposed to storm surge hazards caused by frequent passing typhoons. Storm surges causing damage and devastation to Batanes' coastal communities are critical given the lack of adequate coastal defenses, as proven by the damage caused by Typhoon Meranti. This threat from storm surges and frequent typhoons is further aggravated by the climate change and the rise in GMSL. Numerically modelling the storm surges during Typhoon Meranti, and incorporating the sea level rise simulations is vital in assessing the long-term vulnerability of Batanes' coastal communities. This study aimed to simulate storm surges during Typhoon Meranti using the Advanced Multi-Dimensional Circulation (ADCIRC) model and to apply a sea-level rise scenario to the validated and calibrated model. The model was calibrated and validated versus tide station observations at Basco Port, Batan Island. The model yielded an RMSE of 14.45% versus the observations. The maximum surges simulated along Batan islands were below 0.50 meters, while it was observed that simulated storm surges in Sabtang island reached 1.50 meters. The sea-level rise scenario simulations were observed to output storm surges 93.65% higher in 2030 than those observed during Typhoon Meranti. It was also observed that the relative difference of the storm surge heights decreased from 2030 to 2100.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Storm surges -- Mathematical models -- Philippines